User Fee Exemption Policy Significantly Improved Adherence to Maternal Health Service Utilization in Bahir Dar City, Northwest Ethiopia: A Comparative Cross-Sectional Study - Marye DM; Debalkie Atnafu D; Belayneh M; Takele Alemu A (Dove Medical Press, 2023)
Demlie Mekonnen Marye,1 Desta Debalkie Atnafu,1,2 Melesse Belayneh,1 Ayenew Takele Alemu3 1Department of Health System Management and Health Economics, School of Public Health, Bahir Dar University, Bahir Dar, Ethiopia; 2International Centre for Evidence in Disability, London School of Hygiene and Tropical Medicine, London, UK; 3Department of Public Health, College of Medicine and Health Sciences, Injibara University, Injibara, EthiopiaCorrespondence: Desta Debalkie Atnafu, Email destad2a@gmail.comBackground: Increasing free and skilled delivery is a top priority in the global effort to reduce maternal and newborn mortality. Reducing user-fees through exemption policy has contributed to universal health coverage. However, there is scant evidence regarding the effect of exempted maternal services on adherence to utilization in Ethiopia. Thus, this study aimed to assess the effect of fee exemption policy on adherence to maternal health service utilization and its predictors.Methods: A community-based comparative cross-sectional study was conducted in Bahir Dar City. A two-stage multistage sampling was employed; 497 women participated. Data were collected by face-to-face interview; entered and cleaned using Epi-Data 3.1. SPSS version 25 was used for further analysis. Bivariable and multivariable logistic regression models were computed to assess the association between explanatory and outcome variables. An adjusted odds ratio with a 95% confidence interval was used to interpret the degree of association. The effect of fee exemption policy on adherence to maternal health service utilization was measured by propensity score matching.Results: The overall adherence to maternal service utilization was 54.2%. Factors associated with adherence to maternal health service utilization were pregnancy complications [AOR: 4.1, 95% CI (2.32, 7.28)], secondary and above education [AOR: 4.6, 95% CI (1.38, 15.08)], early ANC1 booking [AOR: 3.1, 95% CI (1.83, 5.16)], autonomous women [AOR: 2.1, 95% CI (1.02, 4.39)], user fee exemption [AOR: 2.3, 95% CI (1.20, 4.47)] and high parity [AOR: 0.39, 95% CI (0.2, 0.75)]. User fee exemption induced a 22.7% increment in adherence to maternal service utilization (ATET=0.227, t=2.13).Conclusion: User fee exemption policy significantly improved adherence to maternal health service utilization. Promoting a fee exemption policy through third-party financing can enhance maternal health service utilization adherence in hard-to-reach settings of Ethiopia by targeting mothers with higher pregnancies, no complications, no autonomy, and less education.Keywords: user fee exemption, maternal health services, Bahir Dar city, Ethiopia